Relevansi Simulasi Permainan â€œHikayat Kerbau Airâ€ Sebagai Media Literasi Perdamaian Bagi Aktivis Aisyiyah - Surwandono, Surwandono; Maksum, Ali (University of Islam Malang, 2020)
This article examined the relevance of game simulation as a model for learning literacy for women activists in sosial and religious isues. Women was peace aktors who have a natural peace instinct compared to men, but in the context of sosial conflict, women's involvement in conflict and peace decision making tends to be minimum. The community services method was conducted by the intervention of knowledge and the value of peace by using the simulation game called â€œHikayat Kerbau Airâ€ or Water Buffalo. The â€œHikayat Kerbau Airâ€ was a game that mobilizes structured experiences that can provide deep scars so that it is expected to be a good stimulus when experiencing similar experiences in the real world. The results of the service interventions showed that the structured experience gained from the â€œHikayat Kerbau Airâ€ game simulation increased the emphatic process and sympathy for the competitors without losing the goals to be achieved. Conflict style choices become more moderate and humanist.